Effects of high-fat diet and physical activity on pyruvate dehydrogenase kinase-4 in mouse skeletal muscle - Rinnankoski-Tuikka Rita (Nutrition & Metabolism, 2012)
Abstract Background The expression of PDK4 is elevated by diabetes, fasting and other conditions associated with the switch from the utilization of glucose to fatty acids as an energy source. It is previously shown that peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), a master regulator of energy metabolism, coactivates in cell lines pyruvate dehydrogenase kinase-4 (PDK4) gene expression via the estrogen-related receptor α (ERRα). We investigated the effects of long-term high-fat diet and physical activity on the expression of PDK4, PGC-1α and ERRα and the amount and function of mitochondria in skeletal muscle. Methods Insulin resistance was induced by a high-fat (HF) diet for 19 weeks in C57BL/6 J mice, which were either sedentary or with access to running wheels. The skeletal muscle expression levels of PDK4, PGC-1α and ERRα were measured and the quality and quantity of mitochondrial function was assessed. Results The HF mice were more insulin-resistant than the low-fat (LF) -fed mice. Upregulation of PDK4 and ERRα mRNA and protein levels were seen after the HF diet, and when combined with running even more profound effects on the mRNA expression levels were observed. Chronic HF feeding and voluntary running did not have significant effects on PGC-1α mRNA or protein levels. No remarkable difference was found in the amount or function of mitochondria. Conclusions Our results support the view that insulin resistance is not mediated by the decreased qualitative or quantitative properties of mitochondria. Instead, the role of PDK4 should be contemplated as a possible contributor to high-fat diet-induced insulin resistance.